Early work experience and the transition into entrepreneurship - Enrico Colombatto; Arie Melnik (The Journal of Entrepreneurial Finance and Business Ventures, 2007)
We use a simple model to analyze the founding stage of new firms. Our goal is to characterize the directional causality between the expected rewards from entrepreneurship and the length of prior labor market experience that entrepreneurs possess. We test predictions about the timing of the formation of new firms on a sample of Italian entrepreneurs. We obtain three main results. First, the timing of the foundation of new firms is determined primarily by the expectation of higher income and not so much by the perception of risk. Second earlier experience of entrepreneurs in full time employment has a positive impact on the size of newly founded firms. Third, founders who work with family partners establish and control larger firms.
Keywords: 650